Regression technique for prediction of salt contamination severity on high voltage insulators - Ahmad, Ahmad S.; Ahmad, Hussein; Salam, Md. Abdus; Saad, Ahmad (2000)
On the east-coast of the Malaysia Peninsular, high voltage insulators of power plants and factories suffer from rapid salt contamination accumulation because of heavy wind coming from the South China Sea. One attempt has been made at one of these plants which is located about 500 meters from the seashore to determine the severity of this kind of contamination and subsequently to determine a suitable mitigation method to overcome this problem. This work describes a mathematical model, which could help to determine the contamination level. It has been proven that the contamination severity predictive model is possible by using a regression technique and it is a useful method for determining the Equivalent Salt Deposit Density (ESDD).